Study of physiological and biophysical processes of degradation of components of the Aral Sea biosystem (Eurasian Journal of Ecology, 2021)
The article considers the results of practical measures to solve environmental problems arising from the fall in sea level and the components of the Aral Sea biosystem, and approaches to their development. A complete literature review of previously planned and identified new environmental problems and practical measures to address the degradation of components of the Aral Sea biosystem is carried out. The research methodology included field studies on changes in the hydrophysical, hydrochemical and hydrobiological state of the landscape, as well as the study of the reference zones of the landscapes and subsequent comparisons with the results of satellite images. The scientific study examines the characteristics of their current state against the background of progressive salinization of the Aral Sea by studying the nature of the horizontal and vertical distribution of bacterio-, phyto- and zooplankton, measuring the concentrations of Chl-а and pheopigments,and determining the taxonomic composition of phyto-and zooplankton. The novelty of the research work for the first time, the consequences of the implementation of new materials, performed scientific research, characterizing the period of development of the problem in 2010-2020, are determined. The results of scientific research can be used for specialists-hydrologists, biologists, ecologists in the formulation of research and scientific and practical work in various landscape zones of the island region, in the preparation of environmental forecasts for the future development of this process.Key words:Aral Sea, phytoplankton, Chl-a, ecological crisis, island degradation, biosystem components, geographical forecast, landscape.